Smart Textile Using Hetero-Core Optical Fiber for Heartbeat and Respiration Monitoring - Koyama, Yuya; Nishiyama, Michiko; Watanabe, Kazuhiro (IEEE sensors journal, 2018)
This paper aims to describe a novel smart textile that uses a single-mode hetero-core optical fiber sensor for monitoring heartbeat and respiration. The smart textile was designed by weaving hetero-core optical fibers together with the wool fabric. This novel textile that can detect variations in shapes can be incorporated into clothes. Such clothes can offer comfort to the wearer. To simultaneously monitor heartbeat and respiration, the proposed textile is sewn on to the clothes to be able to sense minute load changes produced by chest movements. The vital signs, which were calculated from the heartbeat and respiration frequency of a healthy adult, while sitting, were in agreement with those verified using commercial monitoring devices. In addition, to confirm the capability of monitoring vital signs, seven monitoring trials were performed in which the subjects were asked to wear and take off the smart cloth. The vital signs rates were successfully extracted within the four beats per minute error by the fiber optic sensor system. The proposed smart textile in clothes can monitor vital signs in daily life activities, such as sitting and standing.